Translational Challenges in Simultaneous Interpreting: A Case Study - Kukić, Marko E. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Simultaneous interpreting, as a demanding discipline, requires advanced language competencies in both working languages, strong cognitive abilities, and a solid understanding of interpreting techniques. As a complex skill that requires thorough study, it is essential to shed light on its fundamental characteristics through a descriptive method. This paper aims to present the challenges and issues that may arise during the process of simultaneous interpreting. The primary focus of this work is an analysis of an interpreter’s performance while rendering a speech from English to Serbian at a United Nations conference. This research paper examines the challenges observed during the simultaneous (conference) interpretation provided on the national broadcasting service, with a focus on interpreting techniques, cognitive processing, and errors that impact message fidelity. Through a translational analysis based on a product-oriented view of quality, the study identifies errors in simultaneous interpreting and distinguishes them from interpreting techniques. The analysis focuses on the linguistic accuracy and completeness of the interpreted output. Linguistic accuracy refers to the correct and faithful rendering of both grammatical structures and semantic content, ensuring that the meaning and form of the source message are preserved. Completeness, in this context, is defined as the accurate transfer of the entire message, including key ideas, speaker intentions, and discourse structure. Delivery related features such as intonation, voice quality, and prosody fall outside the scope of this study. The descriptive analysis of the interpreted segments of the speech reveals that most problems stem from cognitive skill deficits, indicating that the interpreter’s insufficiently developed memory processes impeded delivery at a high level of accuracy.